Material Structure Design of High-Gain and Low-Noise Multi-Gain-Stage Avalanche Photodiode - Lihong Han; Meiqin Du; Xiaoning Guan; Tong Sun; Gang Liu; Pengfei Lu (Photonics)
In this work, the InGaAs/InAlAs multi-gain-stage APD model is established. The gain and the noise performance of multi-gain-stage APDs are analyzed based on DSMT. By studying the influence of different doping concentrations of the dropping layer and the charge layer on the gain and noise characteristics of the device, the photocurrent, dark current, noise, and gain characteristics of the device are analyzed, and the device structure is optimized. The results show that the maximum gain of the three-gain-stage APD is 416, and the noise factor is 3.5 when the gain is 100. The five-gain-stage APD has a maximum gain of 450 and a noise factor of 4.5 when the gain is 100. The maximum gain of the 10-gain-stage APD can reach more than 850, and the noise factor reaches 6.5 when the gain is 100.